2020
DOI: 10.1002/ejp.1677
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in chronic pain research

Abstract: Background and ObjectiveMetabolomics deals with the identification and quantification of small molecules (metabolites) in biological samples. As metabolite levels can reflect normal or altered metabolic pathways, their measurement provides information to improve the understanding, diagnosis and management of diseases. Despite its immense potential, metabolomics applications to pain research have been sparse. This paper describes current metabolomics techniques, reviews published human metabolomics pain researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…The bioinformatic analysis of CSF proteins related to neuropathic pain gathered from multiple studies [ 66 ] identified three groups of proteins involved in inflammatory responses (APO A1, APO C1 [ 49 ], SERPIN F1), immune responses (ectonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2), transthyretin (TTR), gelsolin (GSN)) and metabolic processes (albumin, prothrombin (F2)), and these were all found changed in our study. The application of metabolomics in pain research is still at an early stage [ 67 ]. Notwithstanding this issue, the metabolomics of the CSF in pain patients revealed that neuropathic pain alters sphingomyelin–ceramide metabolism, nervous tissue damage (alanine, taurine) and inflammatory processes (choline) [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioinformatic analysis of CSF proteins related to neuropathic pain gathered from multiple studies [ 66 ] identified three groups of proteins involved in inflammatory responses (APO A1, APO C1 [ 49 ], SERPIN F1), immune responses (ectonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2), transthyretin (TTR), gelsolin (GSN)) and metabolic processes (albumin, prothrombin (F2)), and these were all found changed in our study. The application of metabolomics in pain research is still at an early stage [ 67 ]. Notwithstanding this issue, the metabolomics of the CSF in pain patients revealed that neuropathic pain alters sphingomyelin–ceramide metabolism, nervous tissue damage (alanine, taurine) and inflammatory processes (choline) [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of metabolomics in pain research is still at an early stage [ 67 ]. Notwithstanding this issue, the metabolomics of the CSF in pain patients revealed that neuropathic pain alters sphingomyelin–ceramide metabolism, nervous tissue damage (alanine, taurine) and inflammatory processes (choline) [ 67 , 68 , 69 ]. Choline, which was found to be elevated in IVDH dogs in our study, is a metabolite related to glial activity, and its elevation was found to be linked with worse pain interference [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 With regard to metabolites, the synovial fluid of patients with chronic symptomatic OA have elevated levels of fructose and citrate and decreased levels of O-acetylcarnitine, N-phenylacetylglycine, methionine, ethanol, creatine, malate, ethanolamine, 3hydroxybutyrate, and hexanoylcarnitine. 10 Significantly depleted serum arginine levels were found in a separate cohort of patients with knee OA. 10 Exosomes derived from mesenchymal stem cells in patients with OA carry substances that decrease the production of inflammatory mediators, including TNF-a, IL-6, prostaglandin-E2, and nitric oxide, and increase the production of the antiinflammatory marker IL-10, in the chondrocytes.…”
Section: Molecular Biomarkersmentioning
confidence: 93%
“…Metabolites have been studied as potential biomarkers of chronic pain conditions. 10 Additionally, exosomesdnanosized extracellular vesicles that carry proteins, lipids, and nucleic acids important in cellular communicationdmay serve as diagnostic markers and therapeutic targets for various chronic pain conditions. 11 Patients with osteoarthritis (OA) have pain with joint movement that may occur at any stage of disease progression.…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…Metabolomics assessment of biological samples (e.g., biofluids, tissue) has emerged as an important precision medicine tool for drug and biomarker discovery, determining drug response phenotypes, and identifying new pathophysiological mechanisms underlying chronic disease 28 31 including vaginal health, 32 34 risk for preterm birth, 35 , 36 and chronic pain conditions including endometriosis. 37 39 Ultimately, metabolomics may serve as a complementary tool to existing experimental approaches that can shed further light on the role sex steroid hormone alterations in PVD.…”
Section: Introductionmentioning
confidence: 99%